Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber - Chen, Zhi-Teng (Zootaxa, 2018)
A new fossil stonefly genus and species of the family Perlidae, Pinguisoperla yangzhouensis gen. et sp. nov., is proposed as the second known genus from mid-Cretaceous Burmese amber. The new genus is characterized by its dark coloration and the basally enlarged and curved cerci. Morphological characters of the new genus and species are described, illustrated, and compared with related taxa.